Analisis Pengolahan Limbah Industri Rokok dalam Pencapaian Standar Lingkungan Badan Air Permukaan - Ramiza Firyal Tuffahati; Rizka Novembrianto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Indonesia's cigarette industry has experienced significant growth, contributing substantially to economic development and work opportunities. However, the production process generates wastewater containing pollutants like BOD, COD, TSS, NH3-N, phenol, and pH imbalances, which pose environmental risks. This study aims to evaluate the quality of wastewater from the cigarette industry and analyze the treatment technologies used to meet environmental standards. Using qualitative methods and secondary data from relevant industries, the research shows that cigarette industry wastewater is highly polluted and requires multiple treatment stages before being discharged into surface water. Key technologies include collecting tanks, equalization tanks, coagulation-flocculation, clarifiers, and trickling filters. The findings provide valuable insights into waste management challenges and propose solutions to support environmental sustainability in the cigarette industry.